Chemical Composition and Antimicrobial Activity of the Essential Oils of Two Aromatic Plants Cultivated in Morocco (Cinnamomum cassia and Origanum compactum) - Asmae Chahbi; Saâdiya Nassik; Hamid El Amri; Ahmed Douaik; El Haj El Maadoudi; Mohamed Boukharta; El Mestafa El Hadrami (Journal of Chemistry)
The present study aims to evaluate the antibacterial properties of natural products according to a pharmacodynamic approach in order to propose them as alternatives to synthetic products. Two essential oils (Cinnamomum cassia and Origanum compactum) were the subject of the chemical and biological study. First, we evaluated the sensitivity of the strains of avian Salmonella to the main antibiotics used and then to the chromatographic analysis of the composition of the two essential oils (EO); finally, we proceeded to the in vitro evaluation of the antibacterial activities of these EO (alone and in combination with antibiotics). The results obtained showed that carvacrol (35.2%), followed by γ-terpinene (20.1%), was the main constituent of the essential oil of O. compactum while cinnamaldehyde (69.1%) represents the major component of the essential oil of C. cassia. The antibioresistance profile of the Salmonella tested showed resistance to ampicillin (35%) and oxytetracycline (41.3%). Active products extracted from the essential oils studied showed antibacterial activity against Salmonella strains. C. cassia products were shown to be more active for Salmonella enteritidis (average inhibition diameter: 16.3 mm) and for Salmonella gallinarum (average inhibition diameter: 27.7 mm). The best synergistic activity with antibiotics has been obtained with the essential oil of C. cassia and its active product cinnamaldehyde. The minimum inhibitory concentration (MIC) of cinnamaldehyde is the lowest (0.05%). The results prove the presence of an antibacterial activity and a synergistic effect of two essential oils studied with the main antibiotics.